Podredumbre de la raíz (Phytophthora cinnamomi Rands) en cultivo de aguacate (Persea americana)” - Leon Placencio, Elmo Emanuel (2024)
The cultivation of avocado (Persea americana Mill) in Ecuador is an important agricultural activity, with specific production areas in provinces such as Carchi, Imbabura, Pichincha, Tungurahua, Azuay, and Loja, located between 1800 and 2600 meters above sea level. This crop faces various challenges, among them, the presence of diseases such as that caused by Phytophthora cinnamomi, a pathogenic oomycete that causes dieback in avocado plants.Symptoms of the disease in avocado crops are severe and involve a number of conditions, such as premature leaf, flower and fruit drop, as well as root and stem rot. These problems can cause significant damage to avocado plantations, affecting both fruit quantity and quality. In addition, it is important to consider the epidemiology of the disease, which highlights the ability of the pathogen to spread through means such as contaminated irrigation water, movement of infected soil and human activity. Therefore, it is critical to implement control and surveillance measures. Several methods have been identified to control the spread of P. cinnamomi, ranging from physical and biological methods to organic and chemical solutions. These range from canopy removal to the use of antagonistic microorganisms, essential oils and biosilica. It is essential to understand the epidemiology of the disease, as well as to adopt preventive measures, such as disinfection of plant material and soil, to reduce the risk of disease spread.